Characteristics of the world`s cassava production with emphasis on Latin America - Díaz, R.O. (International Center for Tropical Agriculture, 1977)
A brief analysis is made of the relative importance of cassava production in relation to other agricultural commodities in casava- producing countries, with emphasis on L.A. World cassava production in 1974 was estimated at 103 million t; Asia and L.A. accounted for 29 percent each and Africa, 42 percent. From 1964-74 production increased 2.9 percent/yr. Area planted was 11 million ha, increasing at a rate of 2.14 percent/yr. Av yield was 9.3 t/ha; yields were lowest in Africa and highest in L.A. Most production comes from small farms, greater than 1 ha. About 56 percent of world production is destined for human consumption. The greatest demand for cassava as animal feed is in the EEC; Thailand supplied 90 percent of this demand with chips and pellets. The only L.A. exporter is Brazil. Implications of changes in supply and demand are discussed with relation to population growth rate production. It is concluded that the best perspectives for developing the feed concentrates industry is using cassava as a source of energy for domestic consumption; for this reason cassava prices must be reduced to levels competetive with those of other substitute products. The possibility of developing cassava starch industries in producing countries should be looked into. (CIAT)